Preparation method of WO3 / TiO2 / MC composite film
Through the preparation method of WO3/TiO2/modified methylcellulose composite film, the problems of uneven element distribution and thickness fluctuation of existing TiO2-doped WO3 films are solved, and better photoelectric and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411369754.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
AI Technical Summary
The existing TiO2-doped WO3 films have uneven element distribution and fluctuations in thickness, resulting in poor optical and electrical performance.
Adopt WO3/TIO2/modified methyl cellulose composite film preparation method, prepare the FTO/TIO2 film through the water thermal method, and mix WO3 colloid with the modified methyl cellulose evenly. Multiple times to ensure uniformity.
Through the synergies of WO3 and TiO2, the unique chemical structure of modified methyl cellulose promotes the separation and charge of electron-floor-to-hole pairs, improving photoelectric performance and mechanical properties, and enhancing the uniformity and consistency of the film.
Smart Images

Figure CN119330606A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a WO 3 / TiO 2 The invention discloses a preparation method of a / MC composite film, and belongs to the technical field of electrochromic materials. Background Art
[0002] The electrochromic layer is the most important core functional part of the entire electrochromic glass device, and its performance directly affects the performance of the electrochromic device. The basic requirements for electrochromic materials are high light transmittance in the faded state, good absorption or reflection characteristics in the colored state, that is, high light modulation amplitude, and good cycle stability, high color change efficiency and fast electrochromic response speed. Electrochromic materials mainly include inorganic electrochromic materials (transition metal oxides and Prussian blue) and organic electrochromic materials. Among them, tungsten oxide (WO3) has attracted widespread attention due to its advantages of high coloring efficiency, good reversibility, and large visible light adjustment range, and has become the most potential electrochromic material. In recent years, research on WO3 has mainly focused on the doping modification and micromorphology control of materials, and has made great research progress. For the doping modification of WO3, some metal elements with lower electronegativity or weaker oxidation ability than W are usually used. Patil et al. also prepared TiO2-doped WO3 thin films and found that the hydrophilicity of TiO2 itself can increase the water content in the film, which is beneficial to the improvement of the electrochromic performance of the film. However, the uneven distribution of elements in the doping preparation process, or the ion migration and charge recombination generated during the electrochemical reaction, lead to the element inhomogeneity and thickness fluctuation of the film, which will affect its optical and electrical properties. Summary of the invention
[0003] The present invention provides a WO 3 / TiO 2 / MC composite film preparation method solves the existing TiO 2 Doped WO 3 The film has uneven element distribution and thickness, resulting in poor optical and electrical properties.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0005] A WO 3 / TiO 2 The preparation method of the / MC composite film comprises the following steps:
[0006] (1) Cleaning the FTO substrate: clean the FTO substrate and set aside;
[0007] (2) Preparation of FTO / TiO 2Thin film: FTO / TiO prepared by hydrothermal method 2 film;
[0008] (3) Preparation of WO 3 The colloid and modified methyl cellulose are mixed evenly to obtain WO 3 Colloid mixture, set aside;
[0009] (4) The FTO / TiO obtained in step 4 2 The thin film substrate is immersed in WO 3 The mixture was placed in the colloidal solution for 20-30 minutes; then rinsed with distilled water and dried with nitrogen. The above operation was repeated 1-5 times to obtain FTO / TiO 2 / WO 3 film;
[0010] The preparation method of the modified methyl cellulose is as follows: dissolving methyl cellulose in deionized water to form an aqueous solution, then sequentially adding chitosan and epichlorohydrin and mixing evenly, reacting at 80°C, rotating at 100 r / min, reacting for 6-8 hours, and then drying and crushing to obtain the modified methyl cellulose.
[0011] Further, preferably: the cleaning FTO substrate is specifically: FTO transparent conductive glass, after using deionized water to blow away the surface dust, use detergent and acetic acid to clean the grease on the substrate surface, and then rinse it with deionized water, and finally use high-pressure dry nitrogen to blow away the residual moisture on the substrate surface.
[0012] Further, preferably: the hydrothermal method for preparing FTO / TiO2 film is as follows: 20 mL of HCl is added to 20 mL of deionized water and magnetically stirred for 10 min at a speed of 150 r / min to fully mix, and then 500 μL of HCl is added. 6 H 36 TiO 4 Stir thoroughly until the solution is clear, transfer the solution to the reactor, and finally place the washed FTO obliquely into the inner lining of the reactor with the conductive surface facing down, transfer it to an oven for hydrothermal reaction at 150°C for 6 hours, cool to room temperature, rinse with deionized water and ethanol, and dry to obtain FTO / TiO2 film.
[0013] Further, preferably: the step (3) is specifically: first dissolving the modified methyl cellulose in distilled water to form an aqueous solution, and then 2 WO 4 Powder water solution, mix well, and then add 30% by mass fraction of H 2 O 2 The solution was added dropwise while stirring at a speed of 150 r / min. After the addition was completed, the temperature was raised to 95°C and stirring was continued for 3 hours to form a stable and transparent WO3 colloidal mixture.
[0014] Further, preferably: the modified methyl cellulose, H 2 WO 4 powder, distilled water and H 2 O 2 The ratio of the solution is 0.35g:3-6g:25ml:4ml.
[0015] Furthermore, preferably, the mass ratio of the methyl cellulose, chitosan, epichlorohydrin and deionized water is 2:1:0.05:196.95.
[0016] Furthermore, preferably, the methyl cellulose has a methoxy content of 27.5-31.5%, a particle size of 100 mesh, and a viscosity of 100 mPa.s.
[0017] Beneficial effects of the present invention:
[0018] The WO3 / TiO2 / modified methyl cellulose composite film of the present invention not only enhances the photoelectric performance, but also improves the mechanical properties and environmental adaptability through the interaction and mutual promotion between the components. The synergistic effect of WO3 and TiO2 can improve the separation efficiency of photogenerated charges. The modified methyl cellulose promotes this separation through its unique chemical structure, which is helpful for the separation of electron-hole pairs. The interface interaction between the modified methyl cellulose and WO3 and TiO2 can regulate the transmission of electrons, which is helpful for improving the mobility of charges and reducing the interface energy barrier. The modified methyl cellulose helps the uniform dispersion of WO3 and TiO2 nanoparticles in the film, increases the contact area between them, and thus increases the active sites of the photocatalytic reaction. The modified methyl cellulose, as a film-forming agent, can effectively improve the uniformity and consistency of the prepared film.
[0019] Modified methyl cellulose has a unique molecular structure and functional groups. These properties enable it to interact with WO3 and TiO2 nanoparticles, preventing the agglomeration of nanoparticles, thereby achieving a more uniform dispersion during the preparation process, allowing each nanoparticle to maintain an independent existence in the film. The nanoparticles are evenly distributed in the film, and the contact area between them is increased. The increase in contact area means that more active sites can be provided for photoelectric reactions. In this way, modified methyl cellulose plays a key role in WO3 / TiO2 composite films, significantly improving the performance of photoelectric reactions by promoting the uniform dispersion of nanoparticles and increasing active sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 A cyclic voltammetry curve of the film prepared by the present invention;
[0022] Figure 2 200 cyclic voltammetry curves of the film prepared by the present invention; DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1-4 Effect of different modified components on WO3 / TiO2 / MC composite film
[0025] A method for preparing a WO3 / TiO2 / MC composite film comprises the following steps:
[0026] (1) Cleaning the FTO substrate: Clean the FTO substrate and set it aside. Specifically, the FTO substrate cleaning comprises: using deionized water to blow away the dust on the surface of the FTO transparent conductive glass, using detergent and acetic acid to clean the grease on the substrate surface, and then rinsing it with deionized water. Finally, using high-pressure dry nitrogen to blow away the residual moisture on the substrate surface.
[0027] (2) Preparation of FTO / TiO2 film: FTO / TiO2 film was prepared by hydrothermal method, specifically: 20 mL of HCl was added to 20 mL of deionized water and magnetically stirred for 10 min at a speed of 150 r / min to fully mix it. Then 500 μL of C16H36TiO4 was added and stirred thoroughly until the solution was clear. The solution was transferred to a reactor. Finally, the cleaned FTO was placed obliquely into the inner lining of the reactor with the conductive surface facing down. The film was transferred to an oven for hydrothermal reaction at 150 °C for 6 h. After cooling to room temperature, it was rinsed with deionized water and ethanol and dried to obtain the FTO / TiO2 film.
[0028] (3) Preparation of WO3 colloid and modified methyl cellulose mixed evenly to obtain WO3 colloid mixed solution, specifically: firstly dissolve the modified methyl cellulose in distilled water to form an aqueous solution, and then2 WO 4 Powder water solution, mix well, and then add 30% by mass fraction of H 2 O 2 The solution was added dropwise while stirring at a speed of 150 r / min. After the addition was completed, the temperature was raised to 95°C and stirring was continued for 3 hours to form a stable and transparent WO3 colloidal solution. 2 WO 4 powder, distilled water and H 2 O 2 The ratio of the solution is 0.35g:4g:25ml:4ml.
[0029] (4) Immerse the substrate of the FTO / TiO2 thin film obtained in step 4 in the WO3 colloidal mixture for 20 minutes; then rinse with distilled water and blow dry with nitrogen gas, repeat the above operation twice to obtain a FTO / TiO2 / WO3 thin film.
[0030] The preparation method of modified methyl cellulose is as follows: dissolve methyl cellulose in deionized water to form an aqueous solution, then add chitosan and epichlorohydrin in sequence and mix evenly, at 80°C, rotate 100r / min, react for 6h, then dry and grind to 100 mesh at 80°C to obtain modified methyl cellulose. Adjust the composition of modified methyl cellulose to investigate the effects of different components on WO3 / TiO2 / MC composite film. The methoxy content of methyl cellulose is 27.5-31.5%, the particle size is 100 mesh, and the viscosity is 100mpa.s.
[0031] The specific ratio of modified methyl cellulose to cellulose is shown in Table 1.
[0032] Table 1 Composition of modified methyl cellulose
[0033] Example 1 Example 2 Example 3 Example 4 Methylcellulose / g 0 2 0 2 Chitosan / g 0 0 1 1 Epichlorohydrin / g 0 0 0 0.05 Deionized water / g 0 198 199 196.95
[0034] Determination of electrochromic properties of prepared FTO / TiO2 / WO3 thin films:
[0035] 1. Cyclic voltammetry curve
[0036] The electrochemical workstation CHI660E was used to test the electrochemical properties of the film; a three-electrode system was used, with the prepared film as the working electrode, platinum wire as the counter electrode, and saturated potassium chloride electrode as the reference electrode. In a 1mol / L LiBF4 / C4H6O3 (lithium tetrafluoroborate / propylene carbonate) electrolyte solution, the cyclic voltage was -1.5V-1.5V, and the scanning rate was 0.1V / s. The CV curves of the first cycle and the 200th cycle were recorded respectively. Cyclic voltammetry is to apply a triangular wave voltage in the form of a fast linear scan, and one triangular wave scan completes a cycle of a reduction process and an oxidation process.
[0037] The results are as follows Figure 1 and 2 According to Q=S / V (where Q is the charge density, S is the area enclosed by the curve, and V is the scan rate), it can be seen that the area of the cyclic voltammetry curve is proportional to the ion storage capacity.
[0038] Depend on Figure 1 It can be seen that Example 1 does not add any additives, Example 2 adds methyl cellulose, Example 3 adds chitosan, and Example 4 adds modified methyl cellulose. The cyclic voltammetry curve areas of Examples 2 and 3 are slightly larger than that of Example 1, but the increase is not obvious; the cyclic voltammetry curve area of Example 4 is significantly larger than that of Example 1, and the increase is significant, indicating that the ion storage capacity is increased.
[0039] Depend on Figure 2 It can be seen that after 200 cycles, the cyclic voltammetry curve areas of Examples 1-3 are significantly reduced, and the cyclic voltammetry curve area of Example 4 is slightly changed, but the change is not too obvious. It can be seen that modified methyl cellulose can effectively increase the electrical properties of the prepared film.
[0040] 2.Li + Diffusion coefficient
[0041] Li + Diffusion coefficient is one of the important parameters to measure the performance of electrochromic film, which represents the coloring efficiency of the film. According to the Randles-Servicik formula: ip = 2.69 × 10 5 n 3 / 2 AD 1 / 2 CV 1 / 2 ;
[0042] Where: n is the charge number, which is 1, ip is the peak current (A), D is Li + Diffusion coefficient (cm 2 / s), A is the effective area of the film (cm 2 ), the value is 3.75cm 2 , C is Li + Concentration (mol / cm 3 ), the value is 1000, V is the scanning rate (V / s), the value is 0.1. Specific data are shown in Table 2.
[0043] Table 2 Li of the films prepared in different examples + Diffusion coefficient
[0044] Example 1 Example 2 Example 3 Example 4 <![CDATA[Li + Diffusion coefficient (cm 2 / s)]]> <![CDATA[1.84×10 -9 ]]> <![CDATA[1.04×10 -9 ]]> <![CDATA[3.36×10 -9 ]]> <![CDATA[4.35×10 -9 ]]> <![CDATA[Li after 200 cycles + Diffusion coefficient (cm 2 / s)]]> <![CDATA[1.86×10 -10 ]]> <![CDATA[3.67×10 -10 ]]> <![CDATA[4.33×10 -10 ]]> <![CDATA[2.63×10 -9 ]]> <![CDATA[Li + Diffusion coefficient reduction rate (%)]]> 90.0 64.7 87.1 39.5
[0045] As shown in Table 2, the addition of modified methyl cellulose can not only effectively improve the Li+ diffusion coefficient of the FTO / TiO2 / WO3 film of the present invention, but also effectively reduce the rate of decrease of the Li+ diffusion coefficient with increasing cycle times. It can be seen that the FTO / TiO2 / WO3 film of the present invention has good film coloring efficiency.
[0046] Example 5
[0047] A method for preparing a WO3 / TiO2 / MC composite film comprises the following steps:
[0048] (1) Cleaning the FTO substrate: Clean the FTO substrate and set it aside; the FTO substrate cleaning method specifically includes: using deionized water to blow away the dust on the surface of the FTO transparent conductive glass, using detergent and acetic acid to clean the grease on the substrate surface, and then rinsing it with deionized water, and finally using high-pressure dry nitrogen to blow away the residual moisture on the substrate surface.
[0049] (2) Preparation of FTO / TiO2 film: FTO / TiO2 film was prepared by hydrothermal method, specifically: 20 mL of HCl was added to 20 mL of deionized water and magnetically stirred for 10 min at a speed of 150 r / min to fully mix it. Then 500 μL of C16H36TiO4 was added and stirred thoroughly until the solution was clear. The solution was transferred to a reactor. Finally, the cleaned FTO was placed obliquely into the inner lining of the reactor with the conductive surface facing down. The film was transferred to an oven for hydrothermal reaction at 150 °C for 6 h. After cooling to room temperature, it was rinsed with deionized water and ethanol and dried to obtain the FTO / TiO2 film.
[0050] (3) Prepare WO3 colloid and modified methyl cellulose and mix them evenly to obtain WO3 colloid mixed solution for standby use; specifically: first dissolve the modified methyl cellulose in distilled water to form an aqueous solution, then add the H2WO4 powder to the aqueous solution, mix evenly, then dropwise add a 30% H2O2 solution by mass, stirring while dropping, the speed is 150r / min, after the dropwise addition, heat to 95°C, continue stirring for 3h, and form a stable and transparent WO3 colloid solution. The ratio of modified methyl cellulose, H2WO4 powder, distilled water and H2O2 solution is 0.35g:3g:25ml:4ml. The preparation method of modified methyl cellulose is as follows: dissolve methyl cellulose in deionized water to form an aqueous solution, then add chitosan and epichlorohydrin in turn and mix evenly, at 80°C, rotate 100r / min, react for 8h, then dry and crush to 100 mesh at 80°C to obtain modified methyl cellulose.
[0051] (4) Immerse the substrate of the FTO / TiO2 thin film obtained in step 4 in the WO3 colloidal mixture for 30 minutes; then rinse with distilled water and blow dry with nitrogen gas, repeat the above operation once to obtain a FTO / TiO2 / WO3 thin film.
[0052] Example 6
[0053] A method for preparing a WO3 / TiO2 / MC composite film comprises the following steps:
[0054] (1) Cleaning the FTO substrate: Clean the FTO substrate and set it aside; the FTO substrate cleaning method specifically includes: using deionized water to blow away the dust on the surface of the FTO transparent conductive glass, using detergent and acetic acid to clean the grease on the substrate surface, and then rinsing it with deionized water, and finally using high-pressure dry nitrogen to blow away the residual moisture on the substrate surface.
[0055] (2) Preparation of FTO / TiO2 film: FTO / TiO2 film was prepared by hydrothermal method, specifically: 20 mL of HCl was added to 20 mL of deionized water and magnetically stirred for 10 min at a speed of 150 r / min to fully mix it. Then 500 μL of C16H36TiO4 was added and stirred thoroughly until the solution was clear. The solution was transferred to a reactor. Finally, the cleaned FTO was placed obliquely into the inner lining of the reactor with the conductive surface facing down. The film was transferred to an oven for hydrothermal reaction at 150 °C for 6 h. After cooling to room temperature, it was rinsed with deionized water and ethanol and dried to obtain the FTO / TiO2 film.
[0056] (3) Prepare WO3 colloid and modified methyl cellulose and mix them evenly to obtain WO3 colloid mixed solution for standby use; specifically: first dissolve the modified methyl cellulose in distilled water to form an aqueous solution, then add the H2WO4 powder to the aqueous solution, mix evenly, then dropwise add a 30% H2O2 solution by mass, stirring while dropping, the speed is 150r / min, after the dropwise addition, heat to 95°C, continue stirring for 3h, and form a stable and transparent WO3 colloid solution. The ratio of modified methyl cellulose, H2WO4 powder, distilled water and H2O2 solution is 0.35g:6g:25ml:4ml. The preparation method of modified methyl cellulose is as follows: dissolve methyl cellulose in deionized water to form an aqueous solution, then add chitosan and epichlorohydrin in turn and mix evenly, at 80°C, rotate 100r / min, react for 7h, then dry and crush to 100 mesh at 80°C to obtain modified methyl cellulose.
[0057] (4) Immerse the substrate of the FTO / TiO2 thin film obtained in step 4 in the WO3 colloidal mixture for 20 minutes; then rinse with distilled water and blow dry with nitrogen gas, repeat the above operation 5 times to obtain a FTO / TiO2 / WO3 thin film.
[0058] The WO3 / TiO2 / MC composite film prepared by the invention has not only good optical and electrical properties, but also good mechanical properties.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a WO3 / TiO2 / MC composite film, characterized in that: The following steps are involved: (1) Cleaning the FTO substrate: clean the FTO substrate and set aside; (2) Preparation of FTO / TiO2 thin film: FTO / TiO2 thin film was prepared by hydrothermal method; (3) preparing WO3 colloid and modified methyl cellulose and mixing them evenly to obtain a WO3 colloid mixed solution for later use; (4) Immerse the substrate of the FTO / TiO2 film obtained in step 4 in the WO3 colloidal mixture for 20-30 minutes; then rinse with distilled water and blow dry with nitrogen, repeat the above operation 1-5 times to obtain a FTO / TiO2 / WO3 film; The preparation method of the modified methyl cellulose is as follows: dissolving methyl cellulose in deionized water to form an aqueous solution, then sequentially adding chitosan and epichlorohydrin and mixing evenly, reacting at 80°C, rotating at 100 r / min, reacting for 6-8 hours, and then drying and crushing to obtain the modified methyl cellulose.
2. The preparation method according to claim 1, characterized in that: The cleaning of the FTO substrate is specifically as follows: FTO transparent conductive glass, after using deionized water to blow away the dust on the surface, use detergent and acetic acid to clean the grease on the substrate surface, then rinse it with deionized water, and finally use high-pressure dry nitrogen to blow away the residual moisture on the substrate surface.
3. The preparation method according to claim 1, characterized in that: The hydrothermal method for preparing FTO / TiO2 film is as follows: 20 mL of HCl is added to 20 mL of deionized water and stirred magnetically for 10 min at a speed of 150 r / min to mix thoroughly, and then 500 μL of C16H 36 TiO4 was fully stirred until the solution was clear, and the solution was transferred to the reactor. Finally, the cleaned FTO was placed obliquely into the inner lining of the reactor with the conductive surface facing down, and transferred to an oven for hydrothermal reaction at 150°C for 6 hours. After cooling to room temperature, it was rinsed with deionized water and ethanol, and dried to obtain the FTO / TiO2 film.
4. The preparation method according to claim 1, characterized in that: The step (3) is specifically as follows: firstly dissolving the modified methyl cellulose in distilled water to form an aqueous solution, then adding the H2WO4 powder into the aqueous solution, mixing evenly, and then dripping a 30% H2O2 solution, stirring while dripping, at a speed of 150r / min. After the dripping is completed, the temperature is raised to 95°C, and the stirring reaction is continued for 3h to form a stable and transparent WO3 colloidal mixed solution.
5. The preparation method according to claim 1, characterized in that: The ratio of the modified methyl cellulose, H2WO4 powder, distilled water and H2O2 solution is 0.35g:3-6g:25ml:4ml.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the methyl cellulose, chitosan, epichlorohydrin and deionized water is 2:1:0.05:196.
95.
7. The preparation method according to claim 1, characterized in that: The methyl cellulose has a methoxy content of 27.5-31.5%, a particle size of 100 meshes, and a viscosity of 100 mpa.s.